“Thoroughly Impregnated with Bolshevik Philosophy”: Annie Buller’s Incarceration and Canadian Political Policing during World War II - Hinther, Rhonda L. (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2024)
Annie Buller makes for an interesting case study of Canada’s World War II security state and how it functioned vis-à-vis the Communist Party of Canada and its allies. Her experiences speak to gender, party history, and broader elements of political policing, community responses, and confinement experiences. Like her life, her wartime encounters with the Canadian security state were concurrently like and different from those of other criminalized female and male activists at the time about whom we know more. Among the apprehended and incarcerated, female or male, Buller was somewhat of an anomaly and warrants special attention. Buller’s particular situation helps to shed light on lesser-understood elements of the Communist wartime carceral experience, including the lack of trust officials had in these processes at times to accomplish the intended repression and important details about efforts to free those incarcerated. Ultimately, Buller’s case and the movement to liberate her and the other incarcerated members of the party illustrate the power of grassroots activism in challenging oppressive systems.